2018
DOI: 10.1088/1361-6528/aaf35c
|View full text |Cite
|
Sign up to set email alerts
|

Study on the oxidation of copper nanowire network electrodes for skin mountable flexible, stretchable and wearable electronics applications

Abstract: Copper nanowires (Cu NWs) are suitable material as an electrode for flexible, stretchable and wearable devices due to their excellent mechanical properties, high transparency, good conductivity, and low cost, but oxidation problem limits their practical use and application. In order to use Cu NWs as an electrode for advanced flexible, stretchable and wearable devices attached directly to the skin, the influence of the body temperature on the oxidation of Cu NWs needs to be investigated. In this paper, the oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Luckily, protection methods for Cu NW TEs have been reported to prolong their long-term stability. Normally, to prevent a Cu NW network from oxidation, the Cu NWs were always coated with a passivation layer, including stable metals or metal oxides, 17,117,118 graphene 119 and organics. 120–123 …”
Section: Protection Of Cu Nws From Oxidationmentioning
confidence: 99%
“…Luckily, protection methods for Cu NW TEs have been reported to prolong their long-term stability. Normally, to prevent a Cu NW network from oxidation, the Cu NWs were always coated with a passivation layer, including stable metals or metal oxides, 17,117,118 graphene 119 and organics. 120–123 …”
Section: Protection Of Cu Nws From Oxidationmentioning
confidence: 99%
“…Cu has received considerable attention as an alternative to ITO and noble metals (Au, Ag) owing to its remarkably low cost and superior electrical conductivity [57][58][59][60][61][62]. Cu has a low electrical resistivity (1.68 μΩ cm), which is similar to that of Ag (1.58 μΩ cm) and lower than that of Au (2.21 μΩ cm), but is 100 times less expensive because it is 1000 times more abundant [63].…”
Section: Cuomentioning
confidence: 99%
“…The transparent conductor made from nanoparticle can be flexible but usually does not work at high stretchable condition. More advanced applications for transparent flexible/transparent conductor can be found in metal nanowires including silver [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and copper [29][30][31][32][33] nanowire percolation networks. Most metal nanowire percolation network research as the ITO replacement started for flexible transparent conductor but recently it was found that the similar metal percolation network can be applied for highly stretchable transparent electrode.…”
Section: Low Temperature Materials Development For Flexible/stretchablmentioning
confidence: 99%